PELAKSANAAN VERIFIKASI DAN FAKTOR PENYEBAB DIKEMBALIKAN KLAIM JAMKESMAS OLEH VERIFIKATOR INDEPENDEN DI RUMAH SAKIT BHAYANGKARA INDRAMAYU - , SHAHNAZ NADIA A.F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In an effort to offset the cost of health care, especially to the patient is not capable, Depkes RI allocates health care through programs Jamkesmas (No. Kepmenkes 125/MENKES/SK/II/2008). Claims Jamkesmas returned by the independent verifier is incomplete supporting documents. Claims bills Jamkesmas patient care with the number of patients less than 55 patients per month, 165 patients within 3 (three) months and there are 36 claims returned within three months in October to December 2013. Objective: To determine the factors causing the patient returned Jamkesmas claims by independent verifier in Indramayu Bhayangkara Hospitals, Knowing verification Jamkesmas patient claims by independent verifiers Indramayu Bhayangkara Hospital, Knowing the obstacles of making claims Jamkesmas in Indramayu Bhayangkara Hospitals. Methode: This study is a descriptive study with a qualitative approach and use the cross-sectional design (cross-sectional). In this study, subjects were selected five (5) people who work in teams to perform verification whereas the object of this study is a document or file archive Jamkesmas claims. The technique of collecting data through observation, interviews, and documentation studies. Results: Factors causing Jamkesmas claim returned in Indramayu Bhayangkara Hospitals of which includes errors and omissions Document Services Administration, Document Administration Membership and Document Administration Finance. The verification of claims Jamkesmas in Indramayu Bhayangkara Hospitals which contain errors in the Implementation and Verification of Claims Administration Services, Implementation of Administrative Claims Verification, Verification of Membership and Implementation of Financial Claims Administration and Barriers in the manufacture of claim Jamkesmas in Indramayu Bhayangkara Hospitals by fishbone theory approach, namely 5M, Man, Money, Methode, Machine and Matherial.